Critical considerations for the practical utility of health equity tools: a concept mapping study - Bernadette Pauly; Wanda Martin; Kathleen Perkin; Thea van Roode; Albert Kwan; Tobie Patterson; Samantha Tong; Cheryl Prescott; Bruce Wallace; Trevor Hancock; Marjorie MacDonald (BMC, 2018)
Abstract Background Promoting health equity within health systems is a priority and challenge worldwide. Health equity tools have been identified as one strategy for integrating health equity considerations into health systems. Although there has been a proliferation of health equity tools, there has been limited attention to evaluating these tools for their practicality and thus their likelihood for uptake. Methods Within the context of a large program of research, the Equity Lens in Public Health (ELPH), we conducted a concept mapping study to identify key elements and themes related to public health leaders and practitioners' views about what makes a health equity tool practical and useful. Concept mapping is a participatory mixed-method approach to generating ideas and concepts to address a common concern. Participants brainstormed responses to the prompt "To be useful, a health equity tool should..." After participants sorted responses into groups based on similarity and rated them for importance and feasibility, the statements were analyzed using multidimensional scaling, then grouped using cluster analysis. Pattern matching graphs were constructed to illustrate the relationship between the importance and feasibility of statements, and go-zone maps were created to guide subsequent action. Results The process resulted in 67 unique statements that were grouped into six clusters: 1) Evaluation for Improvement; 2) User Friendliness; 3) Explicit Theoretical Background; 4) Templates and Tools 5) Equity Competencies; and 6) Nothing about Me without Me- Client Engaged. The result was a set of concepts and themes describing participants' views of the practicality and usefulness of health equity tools. Conclusions These thematic clusters highlight the importance of user friendliness and having user guides, templates and resources to enhance use of equity tools. Furthermore, participants' indicated that practicality was not enough for a tool to be useful. In addition to practical characteristics of the tool, a useful tool is one that encourages and supports the development of practitioner competencies to engage in equity work including critical reflections on power and institutional culture as well as strategies for the involvement of community members impacted by health inequities in program planning and delivery. The results of this study will be used to inform the development of practical criteria to assess health equity tools for application in public health.